PEMAHAMAN TENTANG ATURAN TATA TERTIB MAHASISWA - Rianto, Hadi; Yuliananingsih, Yuliananingsih (JURNAL PENDIDIKAN KEWARGANEGARAAN, 2017)
Understanding of the rules of student discipline is carried out in the study program of PPKN IKIP-PGRI Pontianak 2017. This research was conducted to obtain objective information about: 1) the rules of student discipline knowledge, 2)  student enforcement awareness, and 3) Punished enforcement violations of student disciplinary rules. This research includes the type of qualitative research with the form of descriptive study. In order to collect the research data well, in this study used direct observation techniques, direct communication techniques (interviews), and documentation techniques. Further data obtained in the analysis by doing data reduction, data presentation, to get conclusions. The result of the research reveals that: 1) Knowledge of the rules of discipline of PPKN study program is good because it has been socialized directly affirmed orally and in writing, PPKN study program students have the awareness to enforce the rules of discipline, and Punisment violation of the rules of discipline of students in IKIP PGRI Pontianak implemented based on the provisions contained in the operational guidelines, in accordance with the forms of violations that are often done by students.Keyword: